The Effect of Profitability, Dividend Policy, Debt Policy, and Firm Age on Firm Value in The Non-Bank Financial Industry - Vidiyanna Rizal Putri; Arinie Rachmawati (Jurnal Ilmu Manajemen & Ekonomika, 2017)
The purpose of this research is to determine the effect of profitability, dividend policy, debt policy, and company age on company value with company size as a control variable. A population of this research is non-bank financial companies listed in Indonesia Stock Exchange (IDX) between 2014-2016. The sampling method that used is purposive sampling method and obtained 38 companies. The independent variable is Return On Equity (ROE) as a measure of profitability, Dividend Payout Ratio (DPR) as a measure of dividend policy, Debt to equity ratio (DER) as a measure of debt policy, and firm age. The dependent variable is Tobins Q as a measure of company value. The control variable is an ln total asset as a measure of firm size. This study uses secondary data that obtained from a financial statement that available on Indonesia Stock Exchange. The results showed that Profitability (ROE), and Debt Policy (DER) have no significant effect, dividend policy has a positive significant effect, and Company age has a negative significant effect on firm value. Meanwhile, the control variable (firm size) have no significant effect on firm value.